Sistem Pengenalan Wajah Dengan Metode Template Matching Untuk Absensi Kelas Berbasis Web - Alvonita, Tresa Citra; Elmayati, E; Santoso, Budi (LPPM STIKOM Tunas Bangsa, 2023)
The problems that are often encountered in collecting attendance data at schools, especially in Indonesia, are still done manually and are very inefficient and ineffective. In Selangit State High School students who still take attendance manually through recording in books. This can lead to inaccuracies and fraud during attendance because books are prone to damage, loss, or being left behind, so that significant data can be lost. Therefore, the use of facial recognition technology which is included in the field of image processing can be used to strengthen the attendance system. Making an attendance application with face recognition using the Template Matching method can help facilitate attendance data collection, prevent inaccuracies and fraud, reduce the risk of data corruption, make it easier to make attendance reports from students, and make attendance activities more efficient. The results showed that the face recognition program using the Template Matching method was used for student attendance at school to make it more effective and efficient.